Greenfinches nesting in algerian orchards delayed their breeding and produced less fledglings in the driest of two years. (January 2021) - Bensouilah, Taqiyeddine; Barrientos, Rafael
Abstract: The matching of breeding with the food peak is one of the most important factors affecting the reproductive success in birds. Weather is known to affect the timing of breeding of many bird species. In arid lands, rainfall is usually the factor that triggers the onset of reproduction, since it commonly anticipates the peak of food through its influence on the vegetation development. In this study we used a granivorous finch (European greenfinch Chloris chloris ) as a model to assess the influence of rainfall and temperature on the onset and performance of breeding. The study was carried out in fruit orchards in Guelma state (Northeastern Algeria) in 2013 and 2014. The comparison of breeding parameters between the two years showed that greenfinches delayed their breeding in the year that the rains fell later and were less abundant, produced smaller broods and had lower fledgling rate. Clutch size decreased with the season progress only this year. We discuss our results in the context of the influence of weather on bird reproduction in arid lands, while providing novel data on a farmland species from a region with little ornithological information.